THE PUBLIC ACCOUNTANT IN THE STRATEGIC ADMINISTRATION OF SMALL BUSINESSES IN RIOBAMBA - Jácome Tamayo, Sandra Patricia; Tapia Bonifaz, Angelita Genoveva; Balseca Castro, Jaqueline Elizabeth (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
The study presents the results on the work performed by the public accountant as an advisor to strategic management in small businesses in Riobamba. For the study, two specific objectives are established, which allow identifying the main accounting-financial problems of small businesses, the functions performed by the accountant within them, the level of participation as an advisor in decision-making and the importance that the Management gives this role. The study has a quantitative and qualitative approach, the techniques used are the documentary and the field, the first one allows to carry out a bibliographic and information review that is in the internet network and articles of scientific journals; while, the field research is based on a questionnaire that collects the necessary information from the study variables. The study sought the criteria of the administrators regarding the importance of the involvement and advice that the accountant must express in the decision-making processes, the majority of the administrators (88%) agree with the need for the accountant to be a permanent advisor for management.